Estland und die Wirtschaftskrise - Raudjärv, Matti (Estonian Discussions on Economic Policy, 2009)
This paper gives a brief overview of the important changes that have taken place in 2007-2008 and by the beginning of 2009 and the resulting problems that have arisen in the Estonian economy (non-conformity between the increase in salaries and increase in labour efficiency, real estate boom and decrease in real estate prices, incorrect economic forecasts, budgeting difficulties, increase in taxes, etc.). The main factors which contributed to the economic crisis in Estonia are dwelt upon. A brief overview of the measures taken by several EU Member States for the alleviation of and getting out of the economic crisis are presented. Forecasts for 2009-2010 are discussed, also the opportunities and choices available to Estonia in the conditions of the crisis, and a few examples are given of the international political relations which have an additional effect on economic crises.